Zic family Evolution, Development and Disease (Advances in Experimental Medicine and Biology,, 2018)
This book provides a comprehensive overview of ZIC-family research. Part1 summarizes the ZIC family in animal evolution and development and presents an overall picture of the ZIC family gene structure in eumetazoan animals, providing an evolutionary hypothesis and reviewing the studies on the role of ZIC family proteins in developmental processes for each animal model. Part 2 shows that the ZIC family are the causative genes for developmental disorders, and discusses the role of the ZIC family in stem cell biology. It also presents studies on the ZIC family in the medical biology field. This interdisciplinary book is a valuable resource not only for those people directly involved in ZIC-family-related research, but also researchers in diverse research fields who are interested in the latest advances in biology and medicine. .